THE INFLUENCE OF CAPITAL ADEQUACY RATIO (CAR) AND NON-PERFORMING LOAN (NPL) ONLOAN DISBURSEMENT (AT FOREIGN EXCHANGE NATIONAL PRIVATE COMMERCIAL BANKS LISTEDON THE IDX FOR THE 2014-2018 PERIOD) - Lara Diniyanti; Arif Maulana; Rega Mawarni Nur Hendarin (Cirebon International Conference on Education and Economics Proceeding, 2024)
Banks are business entities that collect funds from the public in the form of deposits and distribute them to the public. The phenomenon that occurs in weak foreign exchange national private commercial banks operating in Indonesia is the poor performance of banks in maintaining the principle of prudence to channel credit funds. Banks concentrate credit on certain individuals or companies so as to encourage high credit risk and have an impact on reducing the quality of productive assets. The purpose of this study was to determine and analyze the effect of Capital Adequacy Ratio (CAR) and Non Performing Loan (NPL) on Lending to Foreign Exchange National Private Commercial Banks listed on the IDX 2014-2018. With a population of 23 companies, sample selection was carried out by using purposive sampling method. This type of research itself is a type of quantitative associative research, which is research that aims to determine a relationship between two or more variables (dependent and independent variables), through data processing in the form of numbers obtained through a study, in this study using secondary data in the form of financial reports of foreign exchange National Private Commercial Bank companies in 2014-2018, then analyzed with several tests. The results showed partially that the Capital Adequacy Ratio (CAR) had a significant effect on Lending, while Non Performing Loan (NPL) had no significant effect on Lending. Simultaneously, the Capital Adequacy Ratio (X1 ) and Non Performing Loan (X2 ) variables have a significant effect on Lending. Bank management should pay more attention to information about the bank’s financial performance and other financial ratios that are useful as an illustration of how the company’s financial condition and analyze banking companies.